Peningkatan Level Keterampilan Guru Sebagai Kader Kesehatan Jiwa di Sekolah Melewati Kegiatan MERAWA-Lah - Lanawati lanawati; Gertrudis Tutpai; Utomo Wicaksono; Dewi Antika Sari (JURNAL SUAKA INSAN MENGABDI (JSIM), 2025)
The success of the mental health component within the Gerakan Sekolah Sehat (Healthy School Movement) depends greatly on educators’ understanding and competencies. At SMA Frater Don Bosco, the school lacked qualified personnel to implement mental health-related activities. Teachers were found unable to perform mental health screening or provide first aid in psychosomatic situations. This community service project aimed to enhance teachers’ skills and empower them to manage the school mental health component effectively. The program was implemented in three stages: socialization, competency training, and evaluation with a follow-up plan. Results showed an improvement in knowledge levels from 35% to 71%, while 100% of participants demonstrated independence in conducting health screening, assessing vital signs, and providing psychological first aid. These findings indicate that the MERAWA-Lah program effectively strengthened teachers’ competencies in supporting school-based mental health promotion.